INFLUENCE OF LIGHT AND TEMPERATURE ON THE DEVELOPMENT OF PROTOCOCCAL ALGAE IN WATER BODIES OF CENTRAL ASIA - Kim S. I.; Davlatova M. J. (Web of Journals Publishing, 2025)
The influence of abiotic factors such as sunlight, temperature, water physicochemical properties, water level, fluctuations, etc. on the development and distribution of algae can be observed in both natural and artificial reservoirs. Many researchers have devoted their work to the ecology of algae. This study examined the effects of illumination and temperature on representatives of Protococcus algae as chlorophyll-containing organisms.
Keywords: Protococcal algae, solar radiation, illumination, photosynthesis rate, water temperature, water transparency.